Impact of Intervention on Innovative Strategies to Optimize Mental Health of Farmers - Patil, M.S. , Khadi P.B (Indian Journal of Extension Education, 2018)
An experimental research was conducted to know the impact of intervention on innovative strategies to optimize mental health of farmers of experimental group in comparison with control group. The total sample of the study comprises 475 farmers. Depression Anxiety Stress Scale developed by Lovibond & Lovibond (1995), Stress- Perceived Stress Scale developed by Sheldon Cohen, (1994), Beck’s Depression Inventory (2004) were used to assess mental health problem such as anxiety disorder and depression, stress and depression level among farmers. Results revealed that the effect scores (Pre test - Post test I) on stress: the farmers of experimental group showed significant decrease in stress score compared to the scores of control group. However, the decrease in the retention scores (Post test I – Post test II) was found to be less among experimental group. In depression, the effect scores of the farmers of experimental group showed significant decrease (14.83) in the depression level compared to the farmers of the control group (6.32). The significant decrease in the retention scores was also found among experimental group. In mental health problems, the decrease in the effect scores of experimental group was found to be -23.00 and for control it was only -7.88, which showed significantly high decrease in the experimental group. The difference in the retention scores was also more in experimental group. However, interactionary effect was found to be significant with both tests and groups. These results highlighted the need for intervention on familial aspects to enhance their overall mental health status.